2019
DOI: 10.15344/2456-8007/2019/137
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction in Patients with Chronic Obstructive Pulmonary Disease: A Meta-Analysis of Case Controlled Studies

Abstract: Background: Chronic obstructive pulmonary disease (COPD) and left ventricular diastolic dysfunction (LVDD) are major causes of morbidity and mortality and have overlapping symptomatology including cough and dyspnea. Whether COPD is a risk factor for LVDD remains largely unclear. The objective of this meta-analysis was to determine if the prevalence of the LVDD as determined by echocardiographic parameters is increased in COPD patients. Methods: We used a time-and-language-restricted search strategy resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…The major findings of our study are: 1) thers is a high frequency—64% (67/104) of stress LVDD / masked heart failure with preserved ejection fraction in non-severe COPD patients with exertional dyspnea was established; 2) some of the cardio-pulmonary exercise testing parameters (peak ‘VO2, ‘VO2 at AT, VE/VCO2 slope, O2pulse and ICdyn) are associated with stress LV E/e’ but none of them is an independent predictor for it; 3) markers of oxidative stress and inflammation are not independent predictors for stress LV E/e’; 4) the combination of the three echocardiographic parameters—RAVI, RV parasternal parameter and RV E/A ratio may independently discern patients with stress LVDD from those without with the accuracy of 91.2%.The first systematic meta-analysis of diastolic dysfunction in COPD revealed that these patients are more likely to have LVDD [ 17 ]. The higher prevalence of LVDD in COPD population is a precondition to HFpEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major findings of our study are: 1) thers is a high frequency—64% (67/104) of stress LVDD / masked heart failure with preserved ejection fraction in non-severe COPD patients with exertional dyspnea was established; 2) some of the cardio-pulmonary exercise testing parameters (peak ‘VO2, ‘VO2 at AT, VE/VCO2 slope, O2pulse and ICdyn) are associated with stress LV E/e’ but none of them is an independent predictor for it; 3) markers of oxidative stress and inflammation are not independent predictors for stress LV E/e’; 4) the combination of the three echocardiographic parameters—RAVI, RV parasternal parameter and RV E/A ratio may independently discern patients with stress LVDD from those without with the accuracy of 91.2%.The first systematic meta-analysis of diastolic dysfunction in COPD revealed that these patients are more likely to have LVDD [ 17 ]. The higher prevalence of LVDD in COPD population is a precondition to HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…ratio may independently discern patients with stress LVDD from those without with the accuracy of 91.2%.The first systematic meta-analysis of diastolic dysfunction in COPD revealed that these patients are more likely to have LVDD [17]. The higher prevalence of LVDD in COPD population is a precondition to HFpEF.…”
Section: Plos Onementioning
confidence: 99%
“…In recent years, several studies have been published signifying the role of diastolic dysfunction in various groups of populations. A higher incidence of diastolic dysfunction has been found in patients with chronic obstructive pulmonary disease (COPD) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Персистирующий неспецифический иммунный ответ респираторной системы на ингаляцию повреждающих частиц сопровождается уклонением цитокинов и других воспалительных факторов в системный кровоток, где они взаимодействуют с сосудистой стенкой и миокардом [10]. Это приводит к ремоделированию сосудов с повышением жесткости сосудистой стенки и прогрессированием атеросклероза, а также к гипертрофии, фиброзу и дисфункции миокарда [11][12][13]. Особый интерес представляет изучение сочетанной формы патологии ПХОБЛ и СН.…”
Section: обоснованиеunclassified